Electronic Health Records (EHR) Usability and User Experience Evaluation: A Case Study - Yunus, Muhammad; Sakkinah, Intan Sulistyaningrum; Rahmawati, Ulfa Emi; Deharja, Atma; Santi, Maya Weka (Universitas Nusantara PGRI Kediri, 2023)
Manual medical record documents have a high risk of leakage and loss. This is because the storage is only in the cupboard. In Indonesia, Electronic Health Records (EHR) have been widely adopted. Clinics, the Rumah Keluarga Sehat Clinic located in Jember Regency. The implemented EHR is a complement to the manual medical record. To obtain a successful EHR implementation, it is necessary to evaluate the usability and user experience. Usability testing is an evaluation method that involves end users in the system development process. This study aims to evaluate the usability and user experience of the EHR developed at the Rumah Keluarga Sehat Clinic. Tests were carried out using the System Usability Scale (SUS) and User Experience Questionnaire (UEQ) instruments. Instruments were given to 7 respondents consisting of doctors, medical recorders, admins, and pharmacists at Rumah Keluarga Sehat Clinic, Jember. The results of the usability evaluation with SUS showed a score of 77.14 which indicated the Good category. And the UEQ results show above-average results on a scale (perspicuity and dependability), and excellent on 4 scales (attractiveness, efficiency, stimulation, and novelty). The results of the evaluation with 2 instruments show that the developed EHR has met the user's needs.